Bioprosthetic mitral valve dysfunction due to native valve preserving procedure. (March 2016) - Matsuno, Yukihiro; Mori, Yoshio; Umeda, Yukio; Takiya, Hiroshi
Mitral valve replacement with preservation of the mitral leaflets and subvalvular apparatus is considered to maintain left ventricular geometry and function and reduce the risk of myocardial rupture. However, the routine use of this technique may lead to early complications such as left ventricular outflow tract obstruction and even mitral inflow obstruction, requiring reoperation. We describe a rare case of bioprosthetic mitral valve dysfunction caused by a native valve preserving procedure.